2019
DOI: 10.1136/vetreccr-2019-000835
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis and dentinogenesis imperfecta in a four‐month‐old English mastiff

Abstract: Osteogenesis imperfecta, also known as ‘brittle bone disease’, is an inherited connective tissue disorder caused by defects in type 1 collagen. The disease results in low bone mass and reduced bone strength, often manifesting as multiple intrauterine fractures, skeletal abnormalities and death before adulthood. A four-month-old, female entire, English mastiff was presented for multiple limb fractures. Due to a poor prognosis, euthanasia was elected. Gross examination revealed diffuse osteopenia with multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“… 12 , 13 Previous histopathological studies of OI found thin trabeculae of woven bone with microfractures, few osteocytes, an absence of secondary spongiosa and osteoblasts containing cytoplasmic vacuoles. 1 , 9 , 11 The patient in the present study showed similar histopathological results and a tentative diagnosis of OI was made after excluding other possible diseases with similar clinical signs.Owing to the poor prognosis, euthanasia is performed in most patients with OI after diagnosis. 1 , 11 Even with surgical repair in a male kitten with suspected OI, which is described in a separate report, the owner went on to elect euthanasia after further fractures were found.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“… 12 , 13 Previous histopathological studies of OI found thin trabeculae of woven bone with microfractures, few osteocytes, an absence of secondary spongiosa and osteoblasts containing cytoplasmic vacuoles. 1 , 9 , 11 The patient in the present study showed similar histopathological results and a tentative diagnosis of OI was made after excluding other possible diseases with similar clinical signs.Owing to the poor prognosis, euthanasia is performed in most patients with OI after diagnosis. 1 , 11 Even with surgical repair in a male kitten with suspected OI, which is described in a separate report, the owner went on to elect euthanasia after further fractures were found.…”
Section: Discussionsupporting
confidence: 72%
“…Owing to the poor prognosis, euthanasia is performed in most patients with OI after diagnosis. 1,11 Even with surgical repair in a male kitten with suspected OI, which is described in a separate report, the owner went on to elect euthanasia after further fractures were found. 14 Unlike veterinary medicine, various treatments, including surgical repair, are carried out in human medicine to improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there was delayed dentition with the dentin layer being subjectively thin, similar to the OI identified in Dachshunds and other breeds. 17,28,[36][37][38] Retrognathism, identified in both puppies, is rare among canine OI case reports, but not uncommon in humans, suggesting a possible difference in presentation in Finnish Lapphund dogs. 39,40 Complete blood cell count, serum chemistry and thyroid hormone testing was performed to assess any abnormalities that might be related to this disorder, and most strikingly there was no rise in alkaline phosphatase enzyme activity typical of puppies undergoing rapid bone turnover, while serum phosphorus was elevated which is typically observed in growing dogs.…”
Section: Discussionmentioning
confidence: 99%